Baseline Maternal and Newborn Variables in a Birth Cohort Study in Southern Brazil - Paulo Floriani Kramer; Elisa Maria Rosa de Barros Coelho; Lívia Mund de Amorim; Gabriela Fernandes Kern dos Santos; Priscila Humbert Rodrigues; Carlos Alberto Feldens (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: Describe baseline maternal and newborn variables in a birth cohort study. Material and Methods: A birth cohort study was conducted in Canoas, Brazil. Sociodemographic, behavioral, anthropometric, and clinical baseline variables from mothers and newborns were collected cross-sectionally at the University Hospital's maternity. Maternal data included age, level of education, family structure, smoking, number of prenatal appointments, type of delivery, gestational age, and any comorbidity. Child data included sex, birth weight, length, head circumference, and breastfeeding in the first hour of life. Data were described as absolute and relative frequency, central tendency, and dispersion measures. Results: The baseline sample comprised 1181 mother-child pairs. Average maternal education (SD) was 9.7 (2.3) years, with 28.3% of mothers not reaching secondary education while 12% were adolescents; number of prenatal appointments was at least 6 in 85.3%, while 58.8% of mothers had comorbidities. Cesarean delivery represented 43.2% of births, with 27.7% of pregnancies not reaching 37 weeks. The prevalence of low birth weight was 6.3%, and 77.1% of children breastfed in the first hour of life. Conclusion:  Baseline data present indicators that should be the subject of public policies and health services programs, with emphasis on a reasonable proportion of mothers with low levels of education and smokers and a high proportion of maternal comorbidities and cesarean deliveries.